2014
DOI: 10.2478/nuka-2014-0023
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle accumulation by aquatic organisms – neutron activation as a tool for the environmental fate of nanoparticles tracing

Abstract: Abstract. Water environments are noted as being some of the most exposed to the infl uence of toxic nanoparticles (NPs). Therefore, there is a growing need for the investigation of the accumulation and toxicity of NPs to aquatic organisms. In our studies neutron activation followed by gamma spectrometry and liquid scintillation counting were used for studying the accumulation of silver nanoparticles (AgNPs) by freshwater larvae of Chironomus and fi sh Danio rerio. The infl uence of exposition time, concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
2
9
0
1
Order By: Relevance
“…40% lower) implied that Ti was still available for organisms. These results clearly show that the bioaccumulation of Ti by D. rerio depends on the source of the NP contamination, which is in agreement with the results of previous studies on the bioaccumulation of silver NPs by the same fish (Asztemborska et al 2014 ). We found that the silver content in D. rerio living in water and containing NPs was 110-fold lower than that in organisms fed with contaminated Chironomid larvae, but remained in the digestive system (Asztemborska et al 2014 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…40% lower) implied that Ti was still available for organisms. These results clearly show that the bioaccumulation of Ti by D. rerio depends on the source of the NP contamination, which is in agreement with the results of previous studies on the bioaccumulation of silver NPs by the same fish (Asztemborska et al 2014 ). We found that the silver content in D. rerio living in water and containing NPs was 110-fold lower than that in organisms fed with contaminated Chironomid larvae, but remained in the digestive system (Asztemborska et al 2014 ).…”
Section: Resultssupporting
confidence: 92%
“…One of the biggest threats of using NPs is the transfer and magnification of these particles in the trophic chain. The studies of silver bioaccumulation by freshwater larvae of the insect Chironomus (diptera: Chironomidae ) and D. rerio fish have shown that the amount of silver uptake by fish depends on the contamination source (Asztemborska et al 2014 ). Larvae that have accumulated silver NPs can be a source of NPs in fish and certainly higher organisms.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies have rarely been conducted with an ionic control or a bulk version of the same materials as the ENPs, and this prevents any firm conclusions with regards to the influence of nanosized particles. In fish, the highest concentration of ENPs has also been found in the gut, whereas elevated concentrations of different ENPs have also been found in, for example, gills, liver, and brain . This shows a potential for translocation, even though the concentrations are lower than the concentrations observed in the gut.…”
Section: Uptake Internalization and Translocation Of Engineered Namentioning
confidence: 99%
“…In this article, authors consider the application of neutron activation as one of the most appropriate methods for detection of accumulation of NPs. Authors emphasized that the transfer of NPs through food led to higher accumulation of Ag NPs compared when they enter into the living organism by consumption of NPs soluble in the water [132]. Y. J. Chae et al carried out the comparative analysis of the effect of Ag ions and Ag NPs on Japanese Medaka (Oryzias latipes) [133].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%